"From Charity to Classroom Co-Learning: Togetherness in the Spirit as a Model for Experiential Education with People with Disabilities". (3rd July 2021) - Raffety, Erin; Carroll, Stuart
Abstract: Reflecting on our experience as educators in a semester long "Disability and Christian Ministry" mini-course with ministerial students from Princeton Theological Seminary (PTS) and Career and Community Studies (CCS) students with I/DD from The College of New Jersey (TCNJ) in Spring 2020, we illuminate the critical role the Spirit and togetherness play in confronting covert ableism in the classroom, disrupting conventional values and power dynamics, and cultivating a new ethos for mutual ministry and leadership. We argue that the dynamic, experiential, and collaborative learning process in the mini- course encouraged students to take greater shared responsibility for their learning in the classroom, equipping them for ministerial leadership by allowing them to experience mutual leadership with one another. The leadership of the Spirit, through the spontaneous distribution of gifts, reconstituted the body, helping PTS and CCS students see themselves as full partners in ministry. However, this article also puts our course in conversation with the broader literature on disability and theological education, emphasizing the need for theological educators to embrace inclusive, experiential theological education as a site for justice and transformation. We make the argument that theological educators, seminaries, and divinity schools must not be satisfied with social programming, community living, or fellowship opportunities with persons with disabilities, but must receive the ministry of people with disabilities in the classroom in order that theological education may be rid of its ableist biases and transformed from the inside out. By withholding classroom space from students with disabilities, theological institutions restrict the dynamic work of the Spirit from the practice of education, hampering the heart of theological education.